2015
DOI: 10.1039/c4ra10197a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and electrochemical characterization of Pt–Pd impregnated nanocomposite polymer electrolyte membranes for high concentration DMFCs

Abstract: Bimetallic Pt-Pd impregnated nanocomposite polymer electrolyte membranes were prepared and the influence of Pd on Pt was evaluated towards a single cell performance. The fabricated membranes were characterised by X-Ray Diffraction (XRD) and Field-Emission Scanning Electron Microscopy (FESEM) attached with Energy Dispersive X-Ray (EDX) spectroscopy for identifying the structural and morphological characteristics, respectively. It was observed that the particle size of the bimetallic particle was increased with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Direct methanol fuel cells (DMFCs) are applied widely in portable and other stationary applications considering its potential as a power source due to its high energy density, ease of storage, and use of liquid as a fuel without any humidification . Many researchers have reported high power density for DMFCs using proton exchange membranes (PEMs) . However DMFC based on PEMs suffer from many limitations such as slow reaction kinetics at anode, methanol cross‐over through the membrane, and high utilization of Pt‐based catalyst in conjunction to cost related issues .…”
Section: Introductionmentioning
confidence: 99%
“…Direct methanol fuel cells (DMFCs) are applied widely in portable and other stationary applications considering its potential as a power source due to its high energy density, ease of storage, and use of liquid as a fuel without any humidification . Many researchers have reported high power density for DMFCs using proton exchange membranes (PEMs) . However DMFC based on PEMs suffer from many limitations such as slow reaction kinetics at anode, methanol cross‐over through the membrane, and high utilization of Pt‐based catalyst in conjunction to cost related issues .…”
Section: Introductionmentioning
confidence: 99%
“…Platinum (Pt) is an effective catalyst for various reactions such as methanol oxidation reaction (MOR) and oxygen reduction reaction (ORR). [1][2][3][4][5] However, its stability, its readiness to be contaminated by carbon monoxide and its high cost are critical issues that need to be addressed. Considerable efforts have been devoted to overcome these problems, predominantly focusing on controlling the morphology, size and composition of Pt-based nanocrystals (NCs).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have been devoted to overcome these problems, predominantly focusing on controlling the morphology, size and composition of Pt-based nanocrystals (NCs). [4][5][6][7][8] For instance, Pt nanorods with a high density of mesopores have exhibited enhanced performance in MOR, compared to Pt nanorods and mesoporous Pt nanoparticles, 9 and concave Pt nanocubes have showed higher electrocatalytic performance for ORR in comparison with normal Pt cubes. 10 Recent progresses have demonstrated that bimetallic Pt-based NCs show improved catalytic activities benchmarked against monometallic Pt NCs.…”
Section: Introductionmentioning
confidence: 99%
“…The methodology used for membrane pre-treatment and Pt-Pd impregnated nanocomposite membrane preparation method has been reported already in our previous work [13].…”
Section: Preparation Of Pt-pd Composite Membranementioning
confidence: 99%